Gender Representation in Indonesian Folktales: A Feminist Analysis of The Origin of Mount Saba Mpolulu and Princess Tandampalik - Afriani Ulya (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2025)
This study explores gender representation in Indonesian folktales through a feminist perspective. The research focuses on two folktales, The Origin of Mount Saba Mpolulu from Southeast Sulawesi and Princess Tandampalik from South Sulawesi, both of which portray complex gender roles and relations. Using a qualitative approach and content analysis method, the study identifies and interprets explicit and implicit elements of gender construction in the narratives. Feminist theory and gender studies are applied as analytical frameworks to examine issues such as subordination, stereotypes, violence, inferiority–superiority, and gender awareness. The findings reveal that folktales reflect not only cultural values but also gender ideologies embedded within society. In The Origin of Mount Saba Mpolulu, the female character demonstrates strength and independence, challenging patriarchal dominance, while also experiencing subordination and stereotyping. In Princess Tandampalik, gender relations are depicted more equally, with both male and female characters exercising autonomy in decision-making despite cultural restrictions. However, traces of gender injustice—such as forced marriage, negative stereotypes, and unequal domestic-public roles—remain evident.